Comparative efficacy of tulathromycin versus a combination of florfenicoloxytetracycline in the treatment of undifferentiated respiratory disease in large numbers of sheep - Champour, Mohsen; Taghipour, Alinaghi (Journal of Advanced Veterinary and Animal Research, 2015)
The objective of this study was to compare the efficacy of tulathromycin (TUL) with a combination of florfenicol (FFC) and long-acting oxytetracycline (LAOTC) in the treatment of naturally occurring undifferentiated respiratory diseases in large numbers of sheep. In this study, seven natural outbreaks of sheep pneumonia in Garmsar, Iran were considered. From these outbreaks, 400 sheep exhibiting the signs of respiratory diseases were selected, and the sheep were randomly divided into two equal groups. The first group was treated with a single injection of TUL (dosed at 2.5 mg/kg body weight), and the second group was treated with concurrent injections of FFC (dosed at 40 mg/kg bwt) and LAOTC (dosed at 20 mg/kg bwt). In the first group, 186 (93%) sheep were found to be cured 5 days after the injection, and 14 (7%) sheep needed further treatment, of which 6 (3%) were cured, and 8 (4%) died. In the second group, 172 (86%) sheep were cured after the injections, but 28 (14%) sheep needed further treatment, of which 10 (5%) were cured, and 18 (9%) died. This study revealed that TUL was more efficacious as compared to the combined treatment using FFC and LAOTC. As the first report, this field trial describes the successful treatment of undifferentiated respiratory diseases in large numbers of sheep. Thus, TUL can be used for the treatment of undifferentiated respiratory diseases in sheep. http://dx.doi.org/10.5455/javar.2015.b86